The evolving culture of medical cannabis in Canada for the management of chronic pain - Clarke, H.; Fitzcharles, M. (Frontiers in Pharmacology, 2023)
Although used therapeutically for millennia, cannabis has been a prohibited substance worldwide for most of the 20th Century. With revision of prohibitive regulations in many jurisdictions during the past two decades, cannabis is increasingly available to patients as a potential treatment option for various symptoms. Pain relief, sleep promotion and alleviation of distress, depression and anxiety are the most common reasons for cannabis use. Canada has been at the forefront of medical cannabis (MC) legislation revisions to enable and facilitate access for therapeutic use. Although initially viewed with caution and stigma, attitudes to cannabis in general have changed. MC is identified as the herbal plant product sourced from a grower/producer and is not at present a regulated pharmaceutical product. MC use is currently prevalent in Canada but has bypassed the rigorous study required for usual drug approval. Although uptake has been enthusiastic by patients, the medical community has voiced cautions and concerns. Access to MC is fairly easy once an approval document is obtained from a healthcare professional, but without obligation for medical or pharmacy oversight. The greatest concern is a dearth of sound clinical evidence for effects and harms. Emerging concerns include prevalent patient self-management with information based on personal research, an abundance of on-line information which may not always be accurate, the emergence of designated “cannabis clinics”, potential risks to society due to accidents, and high cost of the legal medical product leading to access via the recreational market. With cannabis now entrenched in Canadian health care, physicians must be sufficiently knowledgeable to provide guidance that is evidence-based and will ensure personal and societal harm reduction. Examination of the changing culture of MC in Canada will provide insight for countries that may be anticipating similar revisions of cannabis regulations to allow cannabis access for their patient population and learn from the issues created by recreational legalization.